β-Carotene and Lycopene Degradation Kinetics of Tarhana Dough During Convective Air Drying and Traditional Drying Methods - TÜMER, Bedriye DAVULCU; ŞİMŞEK, Ömer; ÖZKAL, Sami Gökhan (Food Science and Technology, 2023)
In this study, tarhana doughs were dried with convective air drying at 30, 40 and 50 oC temperatures and 0.5, 1.25 and 2 m/s air velocities, and with traditional drying (sun-drying method). By this way effects of drying air temperature and velocity on degradation kinetics of β-carotene and lycopene during air drying of tarhana samples were investigated and the results compared with traditional drying method. The degradation reaction of β-carotene and lycopene was found to be following the first-order kinetic model. The reaction rate constant values of the β-carotene degradation were determined in the range of 0.0003-0.0025 min-1, and the activation energy values were determined in the range of 6.15-49.05 kJ/mol. The reaction rate constant values of the lycopene degradation were determined in the range of 0.0001-0.0007 min-1, and the activation energy values were determined in the range of 20.5-34.3 kJ/mol. β-carotene and lycopene content of tarhana samples decreased with the increase in drying temperature, and the rate of degradation reactions of these components increased with the increase in temperature and air velocity. As a result, it was determined that β-carotene and lycopene were better preserved at 1.25 m/s air velocity at 30 oC.